Is functional training an efficient approach to improve body composition in older people? A systematic review - Monteiro, Marcos Raphael Pereira; Cardoso, Alan Pantoja; de Resende-Neto, Antônio Gomes; Vasconcelos, Alan Bruno Silva; Camargo, Enilton Aparecido; Gobbo, Luis Alberto; Maté-Muñoz, José Luis; Heredia-Elvar, Juan Ramón; Behm, David George; Da Silva-Grigoletto, Marzo Edir (Frontiers in Physiology, 2023)
Increases in fat mass and reductions in lean mass are associated with the frailty and mortality of older adults. In this context, Functional Training (FT) is an option to increase lean mass and reduce fat mass in older people. Thus, this systematic review aims to investigate the effects of FT on body fat and lean mass in older adults. We included randomized controlled clinical trials, with at least one intervention group that employed FT, with the age of participants > 60 years; and participants physically independent and healthy. We performed the systematic investigation in Pubmed MEDLINE, Scopus, Web of Science, Cochrane Library, and Google Scholar. We extracted the information and used the PEDro Scale to assess the methodological quality of each study. Our research found 3056 references with five appropriate studies. Of the five studies, three presented reductions in fat mass, all of them with interventions between three and six months, different training dose parameters, and 100% of the sample was composed of women. On the other hand, two studies with interventions between 10 and 12 weeks presented conflicting results. Despite the limited literature about lean mass, it appears that long-term FT interventions may reduce fat mass in older women.